MgB2/NaNO2-PVA free-standing polymer composite film as a green firework: a step towards environmental sustainability - Jeyavani, Vijayakrishnan; Kumar, Rajendra; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (Bulletin of Materials Science, 2022)
We have demonstrated a simple fabrication methodology of free-standing polymer composite film firework that sparkles, provides colour display and moderate sound, yet is less polluting. The polymer composite film fireworks are composed of magnesium boride (MgB2), sodium nitrite (NaNO2) and poly(vinyl alcohol) (PVA). This study also suggested that a flammable, explosive powder composition can be made of two very common inorganic precursors, mainly NaNO2 and MgB2 . This is the first report demonstrating composite film fireworks with new flammable composition using metal boride as a primary precursor, which can also be used in conventional fireworks fabrication, replacing the traditional fuel, mainly gunpowder. The film fireworks were free from charcoal, sulphur, metal powder and paper. Therefore, they substantially lower the odour and COx, NOx, emissions and minimize the substantial trash generated when burned. Most importantly, film firework's minimum ignition temperature and exothermic decomposition temperature are much higher than the ambient temperature; hence are safe to handle.
Keywords: Firework; free-standing film; magnesium boride (MgB2); poly(vinyl alcohol) (PVA); sodium nitrite (NaNO2)

Use of isoperibolic reaction calorimeter for the study of reaction kinetics of acetic anhydride hydrolysis reaction: effect of acetic anhydride and water ratio - Kumar, Rajendra; Tiwari, Anurag Kumar (Chemical and Process Engineering-Inzynieria Chemiczna I Procesowa, 2022)
Reaction kinetics of acetic anhydride hydrolysis reaction is being studied at a fixed reaction temperature and ambient pressure using an isoperibolic reaction calorimeter. Temperature versus time data along with heat and mass balance is used to determine the kinetics parameters i.e. activation energy and Arrhenius coefficient. It has been studied with the varying volumetric ratio of acetic anhydride and water; and kinetics parameters were compared and plotted for each ratio. Such a study has not been done previously to determine the kinetics dependency on varying the acetic anhydride water ratio. As the acetic anhydride hydrolysis reaction is exothermic in nature, the present study will help to decide the safe and suitable operating conditions such as concentration and temperature for conducting this reaction at plant scale. The kinetic data presented can be used further for the mathematical modeling and simulation of such exothermic hydrolysis reactions.
Keywords: acetic anhydride; Hydrolysis; kinetics; reaction calorimeter; Water

A detailed study on heat of reaction and heat rate determination of nitrobenzene hydrogenation to aniline reaction using power compensation reaction calorimeter - Kumar, Rajendra; Mane, Pradip R.; Shingote, Savita K.; Mali, Nilesh A. (Process Safety Progress, 2025)
The present study reports experimental heat of reaction and heat rate data of nitrobenzene hydrogenation to aniline reaction with process parameter variation. A high-pressure isothermal power compensation reaction calorimeter was used for this work. A systematic and step-by-step procedure is also reported to determine the heat of reaction and heat rate for a highly exothermic reaction. The sensitivity of experimental molar heat of reaction (kJ/mol) and evolved heat rate (W) values for nitrobenzene hydrogenation reaction was analyzed for various important process parameters, such as temperature, pressure, substrate quantity, solvent quantity, catalyst quantity, RPM, and hydrogen feed rate. Nitrobenzene hydrogenation reactions were conducted using ethanol as solvent and 5% Pd/C as a catalyst with 55-65 degrees C temperature and 7-9 Bar absolute pressure range. More than 99.99% conversion of nitrobenzene to aniline was obtained, and no other by-products were found. The average experimental nitrobenzene hydrogenation heat of reaction of 21 different experiments was found to be -581.87 kJ/mol, and the maximum heat rate during the nitrobenzene hydrogenation reaction was found to be 16.16 W for experiments using 10 gm of nitrobenzene in solvent.
Keywords: heat of reaction; heat rate; Hydrogenation; nitrobenzene; power compensation; reaction calorimeter